FAKTOR DETERMINAN KEJADIAN IKTERIK NEONATORUM PADA BAYI DI RSUD SAWAHLUNTO - Merianti, Liza (Coping: Community of Publishing in Nursing; Vol 10 No 2 (2022): April 2022DO - 10.24843/coping.2022.v10.i02.p13, 2022)
Neonatal jaundice occurs in newborns in the form of physiological and pathological. Neonates produce two to three times higher bilirubin than adults. Many factors can directly or indirectly cause jaundice, such as maternal, perinatal, and neonatal factors. The purpose of this study was to determine the determinants of the incidence of neonatal jaundice in infants. This type of research is a correlation with a cross sectional research design. The population is all infants aged 0-28 days with a sampling technique using total sampling as many as 31 samples. Data analysis used univariate and bivariate. The results showed that 58,1% of the respondents had a caesarean section, 51,6% had insufficient breast milk intake, 67,7% of the respondents were born with normal weight and 64,5% of respondents were born at term. The results of the bivariate test showed that there was a relationship between gestational period, breast milk intake, birth weight with the incidence of neonatal jaundice (p value 0,003; 0,001; and 0,015). There was no relationship between the type of delivery and the incidence of neonatal jaundice (p value 0,696). The factor that most influenced the incidence of neonatal jaundice was breast milk intake (p value 0,001).